1999
DOI: 10.1016/s0005-2736(99)00081-4
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous administration of superoxide dismutase entrapped in long circulating liposomes

Abstract: Rheumatoid arthritis (RA) is a prevalent and debilitating autoimmune disease that affects the joints. RA is characterized by an infiltration of the affected joint by blood-derived cells. In response to activation, these cells generate reactive oxygen species, resulting in an oxidative stress situation. One approach to counteract this oxidative stress situation is the use of antioxidants as therapeutic agents. The free radical scavenger enzyme superoxide dismutase (SOD) may be used as a therapeutic agent in rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 33 publications
0
58
0
Order By: Relevance
“…Diverse chemical modifications of SOD have been designed to prolong the circulation time and improve its delivery, including coupling with polyethylene glycol, mannose, succinylate, and putrescine encapsulation into liposomes (Freeman et al, 1983;Fujita et al, 1992;Corvo et al, 1999). Some of these derivatives (e.g., polyethylene glycol -SOD, and some SOD mimetics) showed enhanced potency in animal models of systemic (e.g., sepsis) and focal oxidative stress (Tamura et al, 1988;Day et al, 1995;Corvo et al, 1999;Duann et al, 2006). Considerable efforts have also been devoted to optimize SOD delivery to endothelial cells, arguably one of the most important therapeutic targets in vascular oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse chemical modifications of SOD have been designed to prolong the circulation time and improve its delivery, including coupling with polyethylene glycol, mannose, succinylate, and putrescine encapsulation into liposomes (Freeman et al, 1983;Fujita et al, 1992;Corvo et al, 1999). Some of these derivatives (e.g., polyethylene glycol -SOD, and some SOD mimetics) showed enhanced potency in animal models of systemic (e.g., sepsis) and focal oxidative stress (Tamura et al, 1988;Day et al, 1995;Corvo et al, 1999;Duann et al, 2006). Considerable efforts have also been devoted to optimize SOD delivery to endothelial cells, arguably one of the most important therapeutic targets in vascular oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Liposomes have attracted considerable interest as targeted drug carriers in infectious diseases. A number of studies have convincingly demonstrated that so-called long-circulating liposomes tend to localize preferentially at foci of infection or inflammation after intravenous administration (1,9,11,17,19). The preferential localization appears to be the result of the inflammatory response provoking a locally increased capillary permeability, allowing liposome extravasation.…”
mentioning
confidence: 99%
“…Preferential localization of SSL at sites of infection or inflammation that have developed outside the MPS has been reported by a number of investigators (7)(8)(9)(10)(11)(12)(13). Which host factors contribute to selective extravasation of SSL at infectious or inflammatory foci is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental models representing a variety of inflammatory and infectious foci outside the MPS, substantial SSL localization at the site of infection has been demonstrated. The presence of an infectious process is essential as SSL localization in uninfected controls is limited (7)(8)(9)(10)(11)(12)(13). Previous reports have suggested that presence of the long circulation property is also essential to achieve significant localization at the target site (5)(6)14).…”
Section: Introductionmentioning
confidence: 99%